PELATIHAN PERPAJAKAN GUNA MENUMBUHKAN KETAATAN KEWAJIBAN PERPAJAKAN TERHADAP UMKM DI WILAYAH KELURAHAN CIPINANG BARU - Mubarok, Ali; Ganar, Yulian Bayu; Dinantara, Muhammad Duddy; Susanto, Susanto; Zulfitra, Zulfitra; Maddinsyah, Ali (LPPM Universitas Pamulang, 2020)
This Community Service aims to introduce taxes to the MSMEs in the Kelurahan Cipinang Baru. Issues raised regarding taxation for MSMEs. Methods The implementation method of this service is carried out in several activities, namely (a). The Preparation Phase includes: (1). Initial survey (2) Consolidation and determination of target locations, (3). Preparation of training materials / materials. The results of this activity are very useful for MSMEs in the Kelurahan Cipinang Baru to add insight and knowledge about MSME taxes.